Reading and writing recipe books, 1550-1800 - DiMeo, Michelle; Pennell, Sara (Manchester University Press, 2013)
This collection of essays provides an overview of new scholarship on recipe books, one of the most popular non-fiction printed texts in, and one of the most common forms of manuscript compilation to survive from, the pre-modern era (c.1550-1800). This is the first book to collect together the wide variety of scholarly approaches to pre-modern recipe books written in English, drawing on varying approaches to reveal their culinary, medical, scientific, linguistic, religious and material meanings. Ten scholars from the fields of culinary history, history of medicine and science, divinity, archaeology and material culture, and English literature and linguistics contribute to a vibrant mapping of the aspirations invested in and uses of recipes and recipe books. By exploring areas as various as the knowledge economies of medicine, Anglican feasting and fasting practices, the material culture of the kitchen and table, London publishing and concepts of authorship and the aesthetics of culinary styles, these eleven essays (including a critical introduction to recipe books and their historiography) position recipe texts in the wider culture of the sixteenth, seventeenth and eighteenth centuries. They illuminate their importance to both their original compilers and users, and modern scholars and graduate students alike --